'If we Can't Have a Conversation with our Past, then What will be Our Future?': HIV/AIDS, Queer Generationalism, and Utopian Performatives in Matthew Lopez's The Inheritance. (9th July 2020) - Hann, Louisa
Abstract: As the HIV/AIDS epidemic approaches its fifth decade, and emerging generations of queer-identified youth experience and conceptualize the virus in new ways, questions surrounding the memorialization and historicization of queer history have arisen within the arts. In the domain of theatre in particular, as mainstream revivals of crisis-era plays such as Larry Kramer's The Normal Heart (1985) and Tony Kushner's Angels in America (1991) proliferate, criticisms have arisen that such revivals feed into a narrative of the so-called 'AIDS nostalgia', pushing the idea that HIV/AIDS is a thing of the past and ignoring the ways in which the virus continues to shape individual social and sexual experiences. Recently, however, new plays such as Jonathan Harvey's Canary (2010), the GHP Collective's The Gay Heritage Project (2013), and Matthew Lopez's The Inheritance (2018) have explicitly addressed this issue, conceptualizing a revised queer politics of HIV/AIDS that transcends Angels ' famous call for 'The Great Work' to begin. This article explores how The Inheritance in particular problematizes 'AIDS nostalgia' and configures novel approaches to the politics of HIV/AIDS in the twenty-first century. Alongside scholarship within the field of queer utopian studies such as José Estaban Muñoz's Cruising Utopia (2009) and Jill Dolan's Utopia in Performance (2005), it analyses the ways in which Lopez's play employs utopian performatives to move towards a new politics of queer heritage.